Two nematicidal furocoumarins from Ficus carica L. leaves and their physiological effects on pine wood nematode (Bursaphelenchus xylophilus). Issue 17 (1st September 2016) - Guo, Qunqun; Du, Guicai; He, Hongwei; Xu, Hongkai; Guo, Daosen; Li, Ronggui
Abstract: The ethanol extract of the Ficus carica L. leaves was tested to show strong nematicidal activity against pine wood nematode (PWN), Bursaphelenchus xylophilus, causing 90.93% corrected mortality within 72 h at 1.0 mg/mL. From the ethyl acetate soluble fraction of the F. carica L. leaves extract, the main nematicidal constituents were obtained by bioassay-guided isolation and identified as linear furocoumarins bergapten(1) and psoralen(2) by mass and NMR spectral data analysis. Bergapten and psoralen had significant nematicidal activity against PWN with the LC50 values of 97.08 aKSnd 115.03 μ g/mL within 72 h, respectively. The two furocoumarins could inhibit the activities of amylase, cellulase and acetylcholinesterase (AchE) from PWN. The morphologies of PWNs changed much after they were treated by bergapten and psoralen. The physiological effects of bergapten and psoralen on PWN might provide helpful clues to elucidate their nematicidal mechanisms. Graphical abstract: